PENGARUH STRATEGI PEMASARAN TERHADAP MINAT BELI KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MODERATING (STUDI KASUS PRODUK UMKM SATE TANJUNG DI DUSUN PRAWIRA KEC. TANJUNG KABUPATEN LOMBOK UTARA) - Aryani, Menik (Universitas Pendidikan Mandalika, 2022)
Abstract : Fish satay is a processed food product made from fresh fish wrapped with yellow spices made from various spices then grilled using coconut shell charcoal. The purpose of this study was to determine the effect of marketing strategy on consumer buying interest with consumer satisfaction as a moderating variable (a case study of the SME product of sate tanjung in Prawira Hamlet, Tanjung Kec., North Lombok Regency). This research was conducted directly in the field using a survey method aimed at obtaining data on consumer respondents and fish satay traders in the North Lombok region. The results showed that the influence of marketing strategy on consumer buying interest with significant consumer satisfaction on the decision to purchase Tanjung fish satay. The index of consumer buying interest in buying Tanjung fish satay was 649% and the consumer satisfaction index was 327% including the 'satisfied' category. The attributes of the Tanjung fish satay criteria that make consumers satisfied are taste with a satisfaction value of 70% (satisfied), product cleanliness with a satisfaction value of 56% (quite satisfied), cleanliness of the sales place with a satisfaction value of 62% (quite satisfied) and the attractiveness of tanjung fish satay with a satisfaction value of 62% (quite satisfied). Consumers still feel